Perilaku Agresivitas Pada Remaja - ., Zubaidah; Saputra, Randi; Danuarta, Dino; Kusuma, Yusuf Adika (Counseling AS SYAMIL: Jurnal Ilmiah Bimbingan Konseling Islam, 2023)
Abstract: Aggression is a form of behavior that can cause harm to both the individual himself and other parties. This form of behavior is called aggressiveness. Intentional behavior must be controlled, therefore an effort is needed to handle it. In general, this behavior often appears at the adolescent stage of development. Through this research, we will discuss the forms of aggressive behavior in adolescents through studies or research results, as well as other scientific references that have been studied previously. The method used in this research is a literature search via Google Scholar and Research Gate. The keywords used in English are "Aggressiveness and Adolescents", while in Indonesian they use "Aggressiveness and Adolescence". The research results show that there are three types of aggression experienced by adolescents, namely physical, verbal and relational aggression. Apart from that, factors that cause aggressive behavior were found. There are differences in aggression based on residence and gender. In relation to treatment, the results of the study show that peace counseling and coping psychoeducation strategies can be used as an approach to dealing with aggressive behavior. Therefore, it can be recommended for future researchers to examine in more depth aggressive behavior in adolescents from various other aspects.